Work Motivation, Work Discipline and Work Environment on Employee Performance in Cooking Oil Producing Companies: Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Perusahaan Produsen Minyak Goreng - Rofik, Abdul; Sari, Herlinda Maya Kumala (Universitas Muhammadiyah Sidoarjo, 2023)
The success of a company is not always measured by how much profit the company gets, but there are other things that are more important, namely Human Resources (HR) within a company. In connection with this, this research is conducted to prove the partial effect of work motivation, work discipline, and work environment on employee performance at PT. New Shoots Lampung. In this study data collection using research instruments namely questionnaires, data analysis is quantitative and statistical. The sample that will be used in this study are employees of PT. Tunas Baru Lampung Tbk Sidoarjo Margarine Division with a total of 60 employees. The data analysis technique in this study used the help of IBM SPSS V.25 software. Based on the tests that have been carried out, the results obtained are that work motivation have an effect to employee performance, work discipline have an effect to employee performance, work environment have an effect to employee performance, work motivation, work discipline, and work environment have an effect to employee performance.